Sustainable Urban Land Management Based on Earth Observation Data—State of the Art and Trends - Elzbieta Bielecka; Anna Markowska; Barbara Wiatkowska; Beata Calka (Remote Sensing)
This paper aims to analyze and synthesize research on sustainable urban land management (SULM) based on earth observation (EO) data. Particular attention is given to the intellectual foundations and emerging trends in the field. We conducted a search in the Web of Science database, identifying over 1600 research papers, primarily journal articles and conference proceedings. A systematic review methodology was employed for both quantitative analysis (e.g., trends in SULM research over time, distribution by country, journal impact, etc.) and qualitative analysis (e.g., intellectual foundations, emerging trends, and research limitations). An analysis of the 50 most cited publications revealed two main research streams, environmental and technological. The environmental one focuses on the assessment and monitoring of ecosystem services and land use change as a key driver of climate change and its environmental impacts, while the technological stream highlights the role of remote sensing and geospatial technologies and their fusion to develop better, more tailored models and indicators. The researchers also highlight the differences in analytical methodology, depending on the scale of the study. Based on a thorough analysis of the scientific literature, we concluded that sustainable land management, especially in urban areas, is currently the only concept that provides the basis for human survival on earth. Furthermore, monitoring SULM and assessing its changes are immensely difficult without earth observation data.